2014
DOI: 10.1371/journal.pcbi.1003813
|View full text |Cite
|
Sign up to set email alerts
|

Protein Surface Softness Is the Origin of Enzyme Cold-Adaptation of Trypsin

Abstract: Life has effectively colonized most of our planet and extremophilic organisms require specialized enzymes to survive under harsh conditions. Cold-loving organisms (psychrophiles) express heat-labile enzymes that possess a high specific activity and catalytic efficiency at low temperatures. A remarkable universal characteristic of cold-active enzymes is that they show a reduction both in activation enthalpy and entropy, compared to mesophilic orthologs, which makes their reaction rates less sensitive to falling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
130
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(150 citation statements)
references
References 29 publications
14
130
0
Order By: Relevance
“…These calculations showed that protein rigidity well outside of the active site is what seems to control the balance between thermodynamic activation parameters (Fig. 1B), and hence also the temperature adaptation of catalytic rates (9). The results showed that it is the internal energy response of the surroundings of the active site, particularly the protein-solvent interfacial surface, that differs between the cold-and warm-adapted enzymes.…”
mentioning
confidence: 86%
See 3 more Smart Citations
“…These calculations showed that protein rigidity well outside of the active site is what seems to control the balance between thermodynamic activation parameters (Fig. 1B), and hence also the temperature adaptation of catalytic rates (9). The results showed that it is the internal energy response of the surroundings of the active site, particularly the protein-solvent interfacial surface, that differs between the cold-and warm-adapted enzymes.…”
mentioning
confidence: 86%
“…However, due to the huge number of degrees of freedom involved, the extensive configurational sampling required to rigorously obtain activation enthalpies and entropies is presently beyond the scope of most quantum mechanics/molecular mechanics methods. The empirical valence bond (EVB) model (11,12) provides a very efficient method for this purpose, because it allows extensive all-atom molecular dynamics (MD) sampling of the reaction system and can be used to directly construct computational Arrhenius plots (8,9). This strategy has also recently been validated both for solution (13) and enzyme (14) reactions and was found to yield activation enthalpies and entropies in excellent agreement with experiment.…”
Section: Significancementioning
confidence: 99%
See 2 more Smart Citations
“…Finally, Åqvist and coworkers have recently reported some very instructive studies that explored the action of coldadapted enzymes, 130 and demonstrated that the temperature adaptation is controlled by the entropic effects of residues on the protein surface, which in turn leads to entropy-enthalpy compensation (and has nothing to do with dynamical effects).…”
Section: Flexibility and Dynamical Effectsmentioning
confidence: 99%